Mechanical Properties and Permeability of Sand Casting Moulds with Eggshells Binder - Maryam Sharifi Jebeli; Wahyu Kurnianto; Wahono Wahono (Universitas Negeri Malang, 2018)
This research aimed to analyse whether or not eggshell could be a potential addition to sand mould composition as a binding material together with bentonite. Different amounts of eggshell material, i.e. 4%, 7%, 10% and 3%, were added to each sample. This study was a type of pre-experimental design called the one-shot case study. Among all sand moulds under study, sample 3 10% ES in dry conditions had the highest tensile, compressive and shear strengths of 0.09 Kg/cm2, 3.11 Kg/cm2 and 1.13 Kg/cm2, respectively. The results of the permeability test with heat treatment at 110˚C for 60 minutes showed that sample 3 10% ES had a permeability value of 178.3 ml/min.